RIPping the skin apart: necroptosis signaling in toxic epidermal necrolysis - Panayotova Dimitrova, Diana; Feoktistova, Maria; Leverkus, Martin (The journal of investigative dermatology, 2015)
Toxic epidermal necrolysis (TEN) is a rare but potentially fatal drug hypersensitivity reaction. Although a number of pathophysiological hints have been identified over the past decade, details of the effector mechanisms within the skin remain obscure. A novel study by Kim et al. now sheds light on its pathophysiology. The investigators demonstrate convincingly that receptor-interacting kinase 3 (RIPK3) levels are upregulated substantially in the lesional skin of patients with TEN and that this is followed by the generation of reactive oxygen species, activation of mixed lineage kinase-like protein, and subsequent necroptotic cell death of keratinocytes. These data suggest that therapies that interfere with RIPK3 activation and necroptosis induction could benefit patients with TEN.